Pulmonary Function Impairment Associated with PM2.5, CO, and CO₂ Exposure in Home-Based Chips Industry Workers in Indonesia: A Cross-Sectional Study - Kautsar, Brilian Monica; Sudarmaji (Gema Lingkungan Kesehatan, 2025)
Wood remains a traditional fuel source for many rural communities, particularly for cooking purposes. The incomplete combustion of wood, combined with prolonged heating of cooking oil at high temperatures, can release harmful carbon compounds and carcinogenic particles, posing significant risks to respiratory health. The World Health Organization (WHO) reported in 2024 that approximately 3.2 million premature deaths annually are attributable to exposure to such pollutants. This study seeks to evaluate pulmonary function impairments among workers employed in chip home industries that predominantly utilize wood as a primary energy source. The research was conducted across two chip-producing home industries located in Senduro Subdistrict, Lumajang Regency. A total of 44 respondents participated through total sampling, where all workers underwent pulmonary function examinations. The average workplace temperature, particularly near cooking pans and wood-burning stoves, was recorded at 34,7 °C. Concentrations of PM2.5 reached 694,8 µg/m³, while CO and CO2 levels were measured at 6 ppm and 4,460 ppm, respectively. Based on the threshold limits established by the Indonesian Ministry of Health—25 µg/m³ for PM2.5, 25 ppm for CO, and 5,000 ppm for CO₂ (Regulation No. 70 of 2016), only PM 2.5 concentrations significantly exceeded the permissible exposure levels. Although most workers reported few respiratory complaints due to perceived adaptation, field assessments revealed that 79% experienced pulmonary function impairment, either restrictive or obstructive types. Statistical analysis revealed a significant association between pulmonary impairment and age (p=0.001) as well as duration of employment (p=0.001). It is therefore recommended that home industry owners improve workplace environments, particularly by optimizing chimney systems and stove combustion processes, to safeguard workers' respiratory health over the long term.